(untitled) (Journal of EAHIL, 2016)
This article uses an evidenced based approach using the finding of the Library Impact Data Project to help market library resources to students at the University of Huddersfield. Initiatives discussed include the roving librarian, desk-top visits and Lemontree (library game). Reading list software is also used to drive usage and the marketing of these services is also discussed. Finally, the paper looks at the use of a marketing placement student in the library.